Mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF (Metal Organic Framework) as well as preparation method and application of mixed matrix membrane

By filling the Pebax polymer membrane with para-phenylenediamine intercalated phosphonic acid MOF nanoparticles, the problem of limited separation performance of phosphonic acid MOF-based hybrid matrix membrane is solved, and a high specific surface area and optimized pore size structure are achieved, which significantly improves the gas separation performance.

CN119793236APending Publication Date: 2025-04-11SHIHEZI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510204785.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The separation performance of phosphonic acid-based MOF-based hybrid matrix membrane is limited by the low specific surface area and irregular pore size structure, resulting in low gas separation efficiency.

Method used

The para-phenylenediamine intercalated phosphonic acid MOF nanoparticles were used as fillers, and the para-phenylenediamine intercalated phosphonic acid MOF with different specific surface areas and pore sizes were prepared by hydrothermal synthesis method. The Pebax polymer was used as a matrix to form a hybrid matrix membrane with high gas separation performance.

Benefits of technology

The specific surface area of ​​the phosphonic acid MOF of the p-phenylenediamine intercalated phosphonic acid is significantly improved, more CO2 adsorption sites are exposed, the solubility of CO2 is enhanced, and the gas selectivity and permeability of the mixed matrix membrane is improved by regulating the pore size structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793236A_ABST
    Figure CN119793236A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of gas membrane separation, and discloses a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF and a preparation method and application thereof.The preparation method comprises the steps that Pebax macromolecules serve as a matrix, p-phenylenediamine intercalated phosphonic acid MOF nanoparticles serve as a filler and are evenly mixed, a membrane casting solution is obtained, and the membrane casting solution is dried after being cast. According to the prepared mixed matrix membrane filled with the p-phenylenediamine intercalated phosphonic acid MOF, the compatibility with a polymer matrix is remarkably improved, so that the gas separation performance of MMMs is effectively improved. And the CO2 permeability and the CO2 / CH4 selectivity of the MMMs are obviously improved. Compared with the unmodified ZnGly MMMs, the CO2 permeability and the CO2 / CH4 selectivity are respectively improved by 3.5% and 17.8%, and the ZnGly MMMs has an important application prospect in the field of CO2 / CH4 mixed gas separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas separation membranes, and in particular relates to a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF, a preparation method and an application thereof. Background Art

[0002] In recent years, the scale of agricultural production has continued to expand, and the waste liquid and solid waste generated have also increased year by year, making biogas fermentation process facilities gradually come into the public eye. However, the residual CO in the biogas (BNG) produced by fermentation 2 It will affect the utilization rate of biogas. Therefore, it is necessary to selectively remove the CO in biogas. 2 Among the many separation methods, membrane separation has gained great popularity in CO separation due to its unique advantages in economy and environmental protection. 2 The separation field has received extensive attention. Among them, mixed matrix membranes (MMMs) have the potential to combine the easy processability of polymers with the excellent gas separation performance of porous fillers. Under the synergistic effect of the two, the separation performance of the membrane is expected to exceed the Robeson upper limit. Mixed matrix membranes have attracted much attention because they combine the advantages of polymer membranes and inorganic membranes.

[0003] At present, the porous fillers in MMMs mainly include metal organic frameworks (MOF), covalent organic frameworks (COF) and hydrogen bond organic frameworks (HOF). Among them, MOF materials have the characteristics of high crystallinity and strong stability. MOF materials can be divided into phosphonic acid MOF materials, carboxylic acid MOF and nitrogen heterocyclic MOF according to the group classification. Among them, phosphonic acid MOF shows good affinity with CO due to its rich P-OH groups. 2 The strong bond energy and high affinity of MOFs significantly outperform other types of MOF materials. 2 The separation field has attracted much attention. At present, the research progress of phosphonic acid MOF-based mixed matrix membranes shows that its rich group advantages can improve the gas separation efficiency of the membrane, but the generally low specific surface area of ​​phosphonic acid MOF-based mixed matrix membranes limits the further improvement of performance, which limits the separation performance of phosphonic acid MOF-based MMMs. Summary of the invention

[0004] The purpose of the present invention is to provide a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF, a preparation method and an application thereof, by using a phosphonic acid MOF with a high specific surface area to expose more action sites and provide more transmission channels for the gas, thereby solving the problem of limited separation performance of phosphonic acid MOF-based MMMs.

[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0006] A method for preparing a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF, comprising: using Pebax polymer as a matrix and p-phenylenediamine intercalated phosphonic acid MOF nanoparticles as a filler, mixing them evenly to obtain a casting liquid, casting the casting liquid and then drying it to obtain a phosphonic acid MOF-based mixed matrix membrane with high gas separation performance.

[0007] Furthermore, p-phenylenediamine intercalated phosphonic acid MOF was prepared by the following process:

[0008] The p-phenylenediamine and N-bis(phosphinoylmethyl)glycine are mixed, zinc nitrate hexahydrate is added, and then the pH is adjusted to 6-7, and the reaction is carried out at 150-180° C. for 3 days.

[0009] Furthermore, the molar ratio of p-phenylenediamine to N-bis(phosphinoylmethyl)glycine is 0.25-1.5:1.

[0010] Furthermore, the molar ratio of zinc nitrate hexahydrate to N-bis(phosphinoylmethyl)glycine is 3.6:1.

[0011] Further, the preparation method of the mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF is prepared by the following process:

[0012] dissolving Pebax in a mixed solution of ethanol and water to obtain a Pebax matrix solution;

[0013] The p-phenylenediamine intercalated phosphonic acid MOF was added to the Pebax matrix solution, cast, and dried.

[0014] Furthermore, the mass fraction of Pebax in the mixed matrix membrane is 4 wt %.

[0015] Furthermore, the mass fraction of p-phenylenediamine intercalated phosphonic acid MOF in the mixed matrix membrane is 2wt%-10wt%.

[0016] Furthermore, the mass ratio of ethanol to water is 7:3.

[0017] A mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF, wherein the specific surface area of ​​the mixed matrix membrane is 52.54 m 3 / g-126.67m 3 / g.

[0018] A mixed matrix membrane filled with p-phenylenediamine-intercalated phosphonic acid MOF in CO 2 / CH 4 Application in the field of separation of mixed gases.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention adopts p-phenylenediamine intercalated phosphonic acid MOF nanoparticles with different specific surface areas and pore sizes as fillers, which not only significantly increases the specific surface area of ​​p-phenylenediamine intercalated phosphonic acid MOF, but also exposes more CO 2 adsorption sites, thereby enhancing the CO 2 The solubility in the mixed matrix membrane is improved by adjusting the pore structure, and the pore size is reduced, thereby effectively improving the gas selectivity and permeability of the mixed matrix membrane (MMMs), providing a new idea for the design of high-performance gas separation membranes.

[0021] Furthermore, the present invention uses a hydrothermal synthesis method to introduce p-phenylenediamine into a phosphonic acid MOF rich in phosphonic acid groups by changing the molar ratio of p-phenylenediamine to N-bis(phosphinomethyl)glycine, thereby preparing p-phenylenediamine intercalated phosphonic acid MOFs with different specific surface areas and pore sizes. In the present invention, as the molar ratio of p-phenylenediamine to N-bis(phosphinomethyl)glycine changes, the pore size of the p-phenylenediamine intercalated phosphonic acid MOF changes, the surface NH group content increases, and the specific surface area shows a trend of first increasing and then decreasing. Among them, the reduction in pore size is beneficial to the screening of gas molecules and the improvement of the selectivity of the mixed matrix membrane; the increase in specific surface area and the increase in NH groups are not only beneficial to the generation of more CO 2 The present invention provides a strategy for designing a phosphonic acid MOF-based mixed matrix membrane with high gas separation performance by adjusting the molar ratio of p-phenylenediamine to N-bis(phosphinomethyl)glycine on the pore structure parameters and action sites of p-phenylenediamine intercalated phosphonic acid MOF. 2 / CH 4 The field of mixed gas separation has important application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0023] Figure 1 It is the gas separation performance diagram of Pebax / ZnGly-Y mixed matrix membrane under dry mixed gas conditions;

[0024] Figure 2 is the nitrogen physical adsorption-desorption curve of ZnGly-pP-X filler;

[0025] Figure 3 is the infrared spectrum of Pebax / ZnGly-pP-Y mixed matrix membrane;

[0026] Figure 4is a gas separation performance diagram of Pebax / ZnGly-pP-Y mixed matrix membrane under dry mixed gas conditions;

[0027] Figure 5 is a gas separation performance diagram of Pebax / ZnGly-pP-Y mixed matrix membrane under wet mixed gas conditions;

[0028] Figure 6 It is the CO of ZnGly and ZnGly-pP-0.5 fillers 2 Physical adsorption curve;

[0029] Figure 7 It is a graph of gas separation performance of Pebax, Pebax / ZnGly-6 and Pebax / ZnGly-pP-8 mixed matrix membranes under dry mixed gas conditions. DETAILED DESCRIPTION

[0030] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0031] In the present invention, Pebax is a polyether-polyamide block copolymer.

[0032] The present invention discloses a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF, which uses Pebax polymer as a matrix and p-phenylenediamine intercalated phosphonic acid MOF (named ZnGly-pP) nanoparticles with adjustable specific surface area as fillers. A casting solution is obtained by physical blending, and the casting solution is dried to obtain a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF, which is denoted as Pebax / ZnGly-pP-XY, wherein X is the molar ratio of p-phenylenediamine to N-bis(phosphinomethyl)glycine, and Y is the mass percentage of the filler in the total system.

[0033] In the present invention, the molar ratio (R Gly / pP ) realizes the change of ZnGly-pP specific surface area and pore size. The molar ratio of p-phenylenediamine to N-bis(phosphinohydroxymethyl)glycine is 0.25-1:1, and the mass percentage of the filler in the mixed matrix membrane is 2-10wt%. Specifically, the steps are as follows:

[0034] (1) Preparation of p-phenylenediamine intercalated phosphonic acid MOF (ZnGly-pP-X)

[0035] The p-phenylenediamine and N-bis(phosphinoylmethyl)glycine are mixed in a certain molar ratio X, and then zinc nitrate hexahydrate is added, and then the pH is adjusted, and then added to a high-pressure reactor, and reacted under certain temperature conditions. Finally, the mixture is washed with water to obtain a ZnGly-pP-X material, wherein the value of X is 0.25-1.5, preferably 0.25:1, 0.5:1, 0.75:1, 1:1 and 1.5:1.

[0036] (2) Preparation of Pebax / ZnGly-pP-XY

[0037] Dissolving Pebax in an ethanol / water mixed solution to obtain a Pebax matrix solution; wherein the mass ratio of ethanol / water is 7:3;

[0038] Then, the ZnGly-pP-X material prepared in step (1) is added to the Pebax matrix solution, and a casting solution is obtained by physical blending. The casting solution is cast, dried at 20-30°C for 24-48 hours, and then dried in a vacuum drying oven at 40°C for 24 hours to obtain a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF, denoted as Pebax / ZnGly-pP-XY, wherein the mass fraction of Pebax is 4wt%, and the Y value in Pebax / ZnGly-pP-XY is 2wt%-10wt%, preferably 2wt%, 4wt%, 6wt%, 8wt% and 10wt%.

[0039] Furthermore, in step (1), the pH value is adjusted to 6-7.

[0040] Furthermore, in step (1), the reaction temperature in the high pressure reactor is 150-180°C

[0041] Furthermore, the reaction time in the high-pressure reactor in step (1) is 3 days.

[0042] Furthermore, in step (1), the value of X in the ZnGly-pP-X material is 0.5.

[0043] The present invention also provides the Pebax / ZnGly-pP-XY mixed matrix membrane in CO 2 / CH 4 Application in the field of separation of mixed gases.

[0044] The mixed matrix membrane of the present invention can be used to separate CO 2 / CH 4 Mixed gas. Its CO 2 Flux is 500-900 barrer (1 barrer = 10 -10 cm 3 cm / cm 2s cmHg), CO 2 / CH 4 The selectivity is 30-50.

[0045] The following examples are provided to facilitate a better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are purchased from conventional biochemical reagent companies unless otherwise specified.

[0046] Example 1: Preparation of ZnGly-pP-X filler

[0047] In this embodiment, the value of X of the filler is 0.5. The specific preparation method comprises the following steps:

[0048] Weigh 2mmol of N-bis(phosphinohydroxymethyl)glycine and 1mmol of p-phenylenediamine, then add 9mL of ultrapure water, and ultrasonically treat the mixture until it is completely dissolved, which is recorded as solution A; then add 9mL of zinc nitrate solution with a concentration of 0.4mol / L to solution A, add ammonia water after thorough mixing, adjust the pH to 6.5, react at room temperature until the solution turns purple, and then transfer to a high-pressure reactor. After reacting at 180°C for 3 days, the product is collected by centrifugation at 10000rpm, washed with ultrapure water 3 times, and dried at 120°C for 24h. The obtained purple powder is ZnGly-pP. It is recorded as ZnGly-pP-0.5.

[0049] Example 2

[0050] In this embodiment, the value of X of the filler is 0.25.

[0051] Same as Example 1, except that the added amount of p-phenylenediamine is 0.5 mmol.

[0052] Example 3

[0053] In this embodiment, the value of X of the filler is 0.75.

[0054] Same as Example 1, except that the amount of p-phenylenediamine added is 1.5 mmol.

[0055] Example 4

[0056] In this embodiment, the value of X of the filler is 1.

[0057] Same as Example 1, except that the added amount of p-phenylenediamine is 2 mmol.

[0058] Example 5

[0059] In this embodiment, the value of X of the filler is 1.5.

[0060] Same as Example 1, except that the added amount of p-phenylenediamine is 3 mmol.

[0061] Figure 2 Shown are the nitrogen physical adsorption-desorption curves of ZnGly-pP-X with different molar ratios of p-phenylenediamine to N-bis(phosphinomethylol)glycine in Examples 1 to 5, Figure 2 The five nitrogen adsorption and desorption curves shown in the figure are all type IV curves, indicating that it has a micro-mesoporous structure. At the same time, it has an H3 type adsorption structure, indicating that its pore size structure is irregular. When the ratio is 0.25, 0.5, 0.75, 1 and 1.5, its specific surface area corresponds to 105.37m 3 / g, 126.67m 3 / g, 95.12m 3 / g, 77.94m 3 / g and 52.54m 3 / g. From the above analysis, it can be found that when the ratio of p-phenylenediamine is 0.5, the specific surface area reaches the maximum value, so the ratio of 0.5 will be used for subsequent performance test experiments.

[0062] Example 6: Preparation of Pebax / ZnGly-pP-Y mixed matrix membrane

[0063] In this example, the ZnGly-pP-0.5 prepared in Example 1 was used as a filler, and Pebax*1657 was used as a membrane matrix material to prepare Pebax / ZnGly-pP-Y mixed matrix membranes with different filler contents (2wt%, 4wt%, 6wt%, 8wt% and 10wt%). The preparation of the mixed matrix membrane is as follows:

[0064] Step (1), preparing ZnGly-pP-0.5, the same as in Example 1;

[0065] Step (2), weigh 0.5269 g of polyether-polyamide block copolymer (Pebax) particles and add them to 15 mL of anhydrous ethanol aqueous solution (the mass ratio of anhydrous ethanol to water is 7:3), and then place the solution in a constant temperature water bath at 80°C and reflux for 2 hours to completely dissolve the Pebax particles, thereby preparing a Pebax polymer solution with a mass fraction of 4 wt%.

[0066] Step (3), weigh 0.0107 g of ZnGly-pP-0.5 prepared in step (1), add it to the Pebax polymer solution prepared in step (2), and obtain a casting solution by physical blending and stirring at room temperature for 4 hours, and cast the casting solution into a clean culture dish and dry it naturally at room temperature for 48 hours. Then, after removing the film, dry it in a vacuum drying oven at 40° C. for 24 hours, and finally obtain a Pebax / ZnGly-pP mixed matrix membrane with a filler mass fraction of 2 wt%.

[0067] Example 7

[0068] Same as Example 6, except that in step (3), 0.0219 g of ZnGly-pP-0.5 is weighed and the mass fraction of the filler is 4 wt %.

[0069] Example 8

[0070] Same as Example 6, except that in step (3), 0.0336 g of ZnGly-pP-0.5 is weighed, and the mass fraction of the filler is 6 wt %.

[0071] Example 9

[0072] Same as Example 6, except that in step (3), 0.0458 g of ZnGly-pP-0.5 is weighed and the mass fraction of the filler is 8 wt %.

[0073] Example 10

[0074] Same as Example 6, except that in step (3), 0.0585 g of ZnGly-pP-0.5 is weighed and the mass fraction of the filler is 10 wt %.

[0075] Embodiment 11

[0076] Step (1), weigh 2mmol of N-bis(phosphinohydroxymethyl)glycine and 1mmol of p-phenylenediamine, then add 9mL of ultrapure water, and ultrasonically treat the mixture until it is completely dissolved, which is recorded as solution A; then add 9mL of zinc nitrate solution with a concentration of 0.4mol / L to solution A, add ammonia water after thorough mixing, adjust the pH to 6, react at room temperature until the solution turns purple, and then transfer to a high-pressure reactor, react at 150°C for 3 days, collect the product by centrifugation at 10000rpm, wash it with ultrapure water 3 times, and dry it at 120°C for 24h, and the obtained purple powder is ZnGly-pP. It is recorded as ZnGly-pP-0.5.

[0077] Step (2) is the same as in Example 1;

[0078] Step (3), weigh 0.0107 g of ZnGly-pP-0.5 prepared in step (1), add it to the Pebax polymer solution prepared in step (2), and obtain a casting solution by physical blending and stirring at room temperature for 4 hours. The casting solution is cast into a clean culture dish and dried naturally at room temperature of 20° C. for 48 hours. After the film is removed, it is dried in a vacuum drying oven at 40° C. for 24 hours to finally obtain a Pebax / ZnGly-pP mixed matrix membrane with a filler mass fraction of 2 wt%.

[0079] Example 12

[0080] Step (1), weigh 2mmol of N-bis(phosphinohydroxymethyl)glycine and 1mmol of p-phenylenediamine, then add 9mL of ultrapure water, and ultrasonically treat the mixture until it is completely dissolved, which is recorded as solution A; then add 9mL of zinc nitrate solution with a concentration of 0.4mol / L to solution A, add ammonia water after thorough mixing, adjust the pH to 7, react at room temperature until the solution turns purple, and then transfer to a high-pressure reactor, react at 160°C for 3 days, collect the product by centrifugation at 10000rpm, wash it with ultrapure water 3 times, and dry it at 120°C for 24h, and the obtained purple powder is ZnGly-pP. It is recorded as ZnGly-pP-0.5.

[0081] Step (2) is the same as in Example 1;

[0082] Step (3), weigh 0.0107 g of ZnGly-pP-0.5 prepared in step (1), add it to the Pebax polymer solution prepared in step (2), and obtain a casting solution by physical blending, stirring at room temperature for 4 hours, and then cast the casting solution into a clean culture dish and dry it at 30° C. for 24 hours. Then, after removing the film, dry it in a vacuum drying oven at 40° C. for 24 hours, and finally obtain a Pebax / ZnGly-pP mixed matrix membrane with a filler mass fraction of 2 wt%.

[0083] Embodiment 13

[0084] Step (1), weigh 2mmol of N-bis(phosphinohydroxymethyl)glycine and 1mmol of p-phenylenediamine, then add 9mL of ultrapure water, and ultrasonically treat the mixture until it is completely dissolved, which is recorded as solution A; then add 9mL of zinc nitrate solution with a concentration of 0.4mol / L to solution A, add ammonia water after thorough mixing, adjust the pH to 6.5, react at room temperature until the solution turns purple, and then transfer to a high-pressure reactor, react at 170°C for 3 days, collect the product by centrifugation at 10000rpm, wash it with ultrapure water 3 times, and dry it at 120°C for 24h, and the obtained purple powder is ZnGly-pP. It is recorded as ZnGly-pP-0.5.

[0085] Step (2) is the same as in Example 1;

[0086] Step (3), weigh 0.0107 g of ZnGly-pP-0.5 prepared in step (1), add it to the Pebax polymer solution prepared in step (2), and obtain a casting solution by physical blending and stirring at room temperature for 4 hours, and cast the casting solution into a clean culture dish and dry it naturally at 25° C. for 48 hours. Then, after removing the film, dry it in a vacuum drying oven at 40° C. for 24 hours, and finally obtain a Pebax / ZnGly-pP mixed matrix membrane with a filler mass fraction of 2 wt%.

[0087] Figure 3 is the infrared spectra of Pebax / ZnGly-pP-Y with different filling amounts in Example 6 to Example 10. Figure 3 It can be found that at 3000cm -1 To 3600cm -1 At 950cm, there is a broad and blunt weak peak, which is the characteristic peak of P-OH. At the same time, as the filler increases, the peak intensity continues to increase. -1 There are characteristic peaks of P-OH and NH near the surface. This phenomenon is due to the formation of a hydrogen bond network between the filler P-OH and the NH on Pebax, which causes a blue shift. -1 There is a characteristic peak of C=O near the surface, which produces a π-π conjugation effect. As the filling amount of the filler increases, the peak begins to red-shift. Through the above analysis, it can be found that the material forms obvious hydrogen bonding and conjugation effects with the mixed matrix membrane, which improves the CO 2 The force of action.

[0088] Performance determination of Pebax / ZnGly-pP-XY mixed matrix membranes

[0089] The mixed matrix membranes Pebax / ZnGly-pP-Y with different filling amounts prepared in Test Examples 6 to 10 were subjected to dry mixed gas performance tests and wet mixed gas performance tests at 25°C and 0.2 MPa. The permeability coefficients P (Barrer) of the mixed matrix membranes to each gas under dry mixed gas conditions were measured by a gas permeation device, and the gas selectivity α was obtained by the ratio of the permeability coefficients of the two gases.

[0090] Figure 4The graph shows the gas separation performance of mixed matrix membrane Pebax / ZnGly-pP-Y with different filling amounts under dry mixed gas conditions. After testing, it can be found that the filling amounts of Pebax / ZnGly-pP-Y are 0wt%, 2wt%, 4wt%, 6wt%, 8wt% and 10wt%, respectively, and their permeability is 156.82Barrer, 178.83Barrer, 199.24Barrer, 216.16Barrer, 269.18Barrer and 261.81Barrer, and their corresponding selectivities are 15.72, 19.05, 22.42, 26.01, 27.70 and 26.58, respectively. By comparing the permeability and selectivity, it can be found that both the permeability and selectivity show a trend of increasing first and then decreasing. When the filling amount is 8wt%, it is the maximum value, which is mainly due to the formation of a hydrogen bond network between the filler and the mixed matrix membrane, which is in line with its regular characteristics.

[0091] Figure 5 The graph shows the gas separation performance of mixed matrix membrane Pebax / ZnGly-pP-Y with different filling amounts under wet mixed gas conditions. After testing, it can be found that the filling amounts of Pebax / ZnGly-pP-Y are 0wt%, 2wt%, 4wt%, 6wt%, 8wt% and 10wt%, respectively, and their permeability is 332.18Barrer, 491.04Barrer, 639.96Barrer, 755.85Barrer, 930.37Barrer and 896.63Barrer, and their corresponding selectivities are 20.52, 25.10, 32.93, 39.80, 49.20 and 43.20, respectively. By comparing the permeability and selectivity, it can be found that both the permeability and selectivity show a trend of increasing first and then decreasing. When the filling amount is 8wt%, it is the maximum value, which is mainly due to the formation of a hydrogen bond network between the filler and the mixed matrix membrane, which is in line with its regular characteristics.

[0092] Comparative Example 1: Preparation of Pebax / ZnGly-Y mixed matrix membrane

[0093] In this comparative example, zinc nitrate hexahydrate and N-bis(phosphinomethyl)glycine were used as the main raw materials to prepare phosphonic acid MOF (ZnGly). At the same time, ZnGly was used as a filler and polyoxyethylene-polyamide block copolymer (Pebax-1657) was used as a membrane matrix material to prepare a Pebax / ZnGly-Y mixed matrix membrane with a filler content (2wt%). The specific preparation method includes the following steps:

[0094] Step (1), preparation of ZnGly. Weigh 2 mmol of N-bis(phosphinohydroxymethyl)glycine, then add 9 mL of ultrapure water, stir the solution until it is completely dissolved, and record it as solution A; then add 9 mL of zinc nitrate solution with a concentration of 0.4 mol / L to solution A, add ammonia water after thorough mixing, adjust the pH to 6.5, react at room temperature until the solution turns white, and then transfer to a high-pressure reactor, react at 180°C for 3 days, collect the product by centrifugation at 10,000 rpm, wash it with ultrapure water 3 times, and dry it at 120°C for 24 hours. The obtained white powder is ZnGly.

[0095] Step (2), weigh 0.5269 g of polyether-polyamide block copolymer (Pebax) particles and add them to 15 mL of anhydrous ethanol aqueous solution (the mass ratio of anhydrous ethanol to water is 7:3), and then place the solution in a constant temperature water bath at 80°C and reflux for 2 hours to completely dissolve the Pebax particles, thereby preparing a Pebax polymer solution with a mass fraction of 4 wt%.

[0096] Step (3), weigh 0.0107 g of ZnGly from step (1). Add it to the Pebax polymer solution prepared in step (2), and obtain a casting solution by physical blending. After stirring at room temperature for 4 hours, cast the casting solution into a clean culture dish and dry it naturally at room temperature for 48 hours. Then, after removing the film, dry it in a vacuum drying oven at 40° C. for 24 hours, and finally obtain a mixed matrix membrane with a filler mass fraction of 2 wt%.

[0097] The preparation method of pure Pebax membrane is different from that of Pebax / ZnGly-Y mixed matrix membrane in that ZnGly does not need to be added in step (3), and the other operation steps are the same.

[0098] Comparative Example 2

[0099] The same as comparative example 1, except that in step 3, the mass of ZnGly is 0.0219 g, and the filler content in the prepared Pebax / ZnGly-Y mixed matrix membrane is 4 wt %.

[0100] Comparative Example 3

[0101] The same as comparative example 1, except that in step 3, the mass of ZnGly is 0.0336 g, and the filler content in the prepared Pebax / ZnGly-Y mixed matrix membrane is 6 wt %.

[0102] Comparative Example 4

[0103] The same as comparative example 1, except that in step 3, the mass of ZnGly is 0.0458 g, and the filler content in the prepared Pebax / ZnGly-Y mixed matrix membrane is 8 wt %.

[0104] Comparative Example 5

[0105] The same as comparative example 1, except that in step 3, the mass of ZnGly is 0.0585 g, and the filler content in the prepared Pebax / ZnGly-Y mixed matrix membrane is 10 wt %.

[0106] Performance determination of Pebax / ZnGly-Y mixed matrix membranes

[0107] The mixed matrix membranes Pebax / ZnGly-Y with different filling amounts prepared in Comparative Examples 1 to 5 were tested for dry mixed gas performance at 25°C and 0.2 MPa. The permeability coefficients P (Barrer) of the mixed matrix membranes to each gas under dry mixed gas conditions were measured by a gas permeation device, and the permeability coefficients of the mixed matrix membranes to each gas under dry mixed gas conditions were measured by CO 2 and CH 4 The gas selectivity α is obtained by the ratio of the permeability coefficients.

[0108] Figure 1 The graph shows the gas separation performance of mixed matrix membrane Pebax / ZnGly-Y with different filling amounts under dry mixed gas conditions. After testing, it can be found that the filling amounts of Pebax / ZnGly-Y are 0wt%, 2wt%, 4wt%, 6wt%, 8wt% and 10wt%, respectively, and their permeability P is 156.82Barrer, 168.13Barrer, 187.96Barrer, 261.81Barrer, 237.60Barrer and 228.63Barrer. At the same time, their corresponding selectivities α are 15.72, 19.19, 19.97, 23.58, 22.31 and 22.54, respectively. By comparing the permeability and selectivity, it can be found that both the permeability and selectivity show a trend of first increasing and then decreasing. When the filling amount is 6wt%, it is the maximum value, mainly because the phosphonic acid MOF material can improve the CO 2 affinity, thus improving the gas transfer effect and thus improving the CO 2 Permeability and selectivity.

[0109] CO of ZnGly and ZnGly-pP-0.5 2 Comparison of physical adsorption performance

[0110] In order to better illustrate the CO 2The physical adsorption performance data is better. ZnGly and ZnGly-pP are subjected to CO under isothermal conditions. 2 Physical adsorption experiments.

[0111] Figure 6 The results show that ZnGly and ZnGly-pP react with CO before and after adding p-phenylenediamine. 2 The results of physical adsorption experiments showed that the addition of p-phenylenediamine effectively improved the material's absorption of CO 2 affinity for CO 2 From the data, we can see that compared with the 3.60 cm of ZnGly 3 / gCO 2 Adsorption amount, CO of ZnGly-pP 2 The adsorption capacity increased to 6.76cm 3 / g.

[0112] Comparison of gas separation performance of pure Pebax membrane, Pebax / ZnGly-6 and Pebax / ZnGly-pP-8 under dry mixed gas conditions

[0113] In order to better illustrate the performance improvement, the data with the best gas separation among Pebax, Pebax / ZnGly-Y and Pebax / ZnGly-pP-Y were selected for comparison. Figure 1 From the data, it can be found that the performance of Pebax / ZnGly-Y is optimal when Y is 6; Figure 4 From the data, we can find that the performance of Pebax / ZnGly-pP-Y is best when Y is 8. Therefore, we draw a graph based on this actual data.

[0114] Figure 7 The gas separation performance of Pebax, Pebax / ZnGly-6 and Pebax / ZnGly-pP-8 under dry mixed gas conditions is shown. By comparing the performance, it is found that Pebax / ZnGly-pP-8 has a CO 2 The permeability and selectivity of CO were higher than those of Pebax and Pebax / ZnGly-6. 2 The permeability and selectivity were increased by 72.5% and 75.7% respectively compared with Pebax, and by 3.5% and 17.8% respectively compared with Pebax / ZnGly-6. This is mainly due to the fact that ZnGly-pP has a higher specific surface area and CO 2 The adsorption capacity can not only increase the CO 2 Gas transfer channel, and also beneficial to improve CO 2On the other hand, ZnGly-pP can form a hydrogen bond network and π-π conjugation effect with Pebax, thereby improving the mixed matrix membrane's resistance to CO 2 Through the synergistic effect of the above two aspects, a tortuous CO 2 The transfer pathways and hydrogen bonding networks act to enhance the permeation-selective properties of mixed matrix membranes and overcome the trade-off effect.

[0115] The present invention forms a new ZnGly-pP material by inserting p-phenylenediamine into ZnGly. The material not only has a higher specific surface area than ZnGly, but also can improve CO 2 By blending ZnGly-pP with Pebax, a rich hydrogen bond network and π-π conjugation effect are formed in the Pebax / ZnGly-pP-8 mixed matrix membrane, thereby improving the permeability-selectivity of the mixed matrix membrane and overcoming the trade-off effect.

[0116] In the synthesis process of phosphonic acid MOF (ZnGly), by introducing p-phenylenediamine and adjusting the molar ratio of p-phenylenediamine to N-bis(phosphinomethyl)glycine (R Gly / pP ), successfully prepared a CO-rich 2 The ZnGly-pP material with amino groups and phosphate groups significantly improves the compatibility with the polymer matrix, thereby effectively improving the gas separation performance of MMMs. 2 The strong selective adsorption of CO 2 Permeability and CO 2 / CH 4 Compared with the unmodified ZnGly MMMs, CO 2 Permeability and CO 2 / CH 4 The selectivity was increased by 3.5% and 17.8% respectively. The present invention solves the problem of limited separation performance of phosphonic acid MOF-based MMMs by designing a high specific surface area phosphonic acid MOF to expose more action sites and provide more transmission channels for gas, and provides a strategy for designing phosphonic acid MOF-based mixed matrix membranes with high gas separation performance. 2 / CH 4 The field of mixed gas separation has important application prospects.

[0117] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0118] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF, characterized in that: Pebax polymer is used as a matrix, p-phenylenediamine intercalated phosphonic acid MOF nanoparticles are used as a filler, the mixture is evenly mixed to obtain a casting solution, the casting solution is cast and then dried to obtain a phosphonic acid MOF-based mixed matrix membrane with high gas separation performance.

2. The method for preparing a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF according to claim 1, characterized in that: The p-phenylenediamine intercalated phosphonic acid MOF was prepared by the following process: The p-phenylenediamine and N-bis(phosphinoylmethyl)glycine are mixed, zinc nitrate hexahydrate is added, and then the pH is adjusted to 6-7, and the reaction is carried out at 150-180° C. for 3 days.

3. The method for preparing a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF according to claim 2, characterized in that: The molar ratio of p-phenylenediamine to N-bis(phosphinohydroxymethyl)glycine is 0.25-1.5:

1.

4. The method for preparing a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF according to claim 2, characterized in that: The molar ratio of zinc nitrate hexahydrate to N-bis(phosphinoylmethyl)glycine is 3.6:

1.

5. The method for preparing a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF according to claim 1, characterized in that: The preparation method of the mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF is prepared by the following process: dissolving Pebax in a mixed solution of ethanol and water to obtain a Pebax matrix solution; The p-phenylenediamine intercalated phosphonic acid MOF was added to the Pebax matrix solution, cast, and dried.

6. The method for preparing a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF according to claim 4, characterized in that: The mass fraction of Pebax in the mixed matrix membrane is 4 wt%.

7. The method for preparing a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF according to claim 4, characterized in that: The mass fraction of p-phenylenediamine intercalated phosphonic acid MOF in the mixed matrix membrane is 2wt%-10wt%.

8. The composite phosphonic acid MOF-based mixed matrix membrane with high specific surface area and strong CO2 adsorption capacity according to claim 4, characterized in that: The mass ratio of ethanol to water is 7:

3.

9. A mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF prepared according to any one of claims 1 to 8, characterized in that: The specific surface area of ​​the mixed matrix membrane is 52.54 m 3 / g-126.67m 3 / g.

10. Use of a mixed matrix membrane filled with p-phenylenediamine intercalated phosphonic acid MOF prepared by the method according to any one of claims 1 to 8 in the field of separation of CO2 / CH4 mixed gases.